2018
DOI: 10.1186/s12905-018-0632-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of domestic violence and associated factors among pregnant women attending antenatal care service at University of Gondar Referral Hospital, Northwest Ethiopia

Abstract: BackgroundDomestic violence during pregnancy with its many negative fetal and maternal outcomes is a common public health problem all over the world. Nonetheless, the problem is not well investigated and understood in Ethiopia. Hence, this study aimed to assess the prevalence of domestic violence and associated factors among pregnant women attending the University of Gondar Referral Hospital antenatal care (ANC) services.MethodsA hospital-based cross-sectional study was conducted from March–May 2016. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
63
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 34 publications
15
63
5
Order By: Relevance
“…According to research conducted in Gonder referral Hospital, the overall prevalence of domestic violence among pregnant women was estimated to be 58.7% with emotional violence being the most common (57.8%), followed by physical violence (32.2%), and sexual violence (7.6%). This research also showed that house wives, women with no salary of their own, partners' daily use of alcohol, and women who disobeyed their partner were found to be positively and significantly associated with domestic violence during pregnancy [13].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…According to research conducted in Gonder referral Hospital, the overall prevalence of domestic violence among pregnant women was estimated to be 58.7% with emotional violence being the most common (57.8%), followed by physical violence (32.2%), and sexual violence (7.6%). This research also showed that house wives, women with no salary of their own, partners' daily use of alcohol, and women who disobeyed their partner were found to be positively and significantly associated with domestic violence during pregnancy [13].…”
Section: Introductionmentioning
confidence: 59%
“…Based on literature, Independent variables included in the analysis are described in Table 1 [12,13,[17][18][19][20][21][22][23][24][25][26].…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…A set of sociodemographic and economic predictor variables were included in the analysis based on their conceptual association with experience of abusive behavior. This was facilitated by a review of the existing literature in other countries in sub-Saharan Africa, including the Democratic Republic of Congo [30], Ethiopia [31], Ghana [32], and Nigeria [33]. The underlying theme that emerged from the review was that women's susceptibility to IPV generally results from low empowerment, such as lower socioeconomic status, as well as behavioral factors embedded in the sociocultural environment, such as ethnic norms, religious guidelines, power relationship in the household (head, wife), and risk factors of abusive behavior (alcohol drinking).…”
Section: Methodsmentioning
confidence: 99%
“…Violence negatively affects women's reproductive health and may increase also the risk of acquiring human immune-deficiency virus (HIV) in some settings [6]. Pregnancy has been identified as a period of increased risk for exposure to violence, and the vulnerability of pregnant women to violence and to their consequences is an alarming public health issue in developing countries [8]. Intimate partner violence (IPV) during pregnancy is of concern as the possible consequences pose risk to both mother and the unborn child [2].…”
Section: Introductionmentioning
confidence: 99%